THE BODY'S HORMONAL RESPONSE UNDER THE INFLUENCE OF AUDITORY STRESS - Razvan Chirica; Gheorghe Ionel Comsa (European Scientific Journal, ESJ, 2013)
Sound causes to the body not only beneficial effects, relaxing by his action, but also harmful effects, by changes, at both, cellular and hormonal level. The effect of repeated exposure to a noise source, on the enzymatic activity of cortisone is found in the present study. The study was conducted on laboratory animals (Wistar rats, albino line) through their exposure for 7 days at a noise source with an intensity of 38 ± 2 db.